EXAMINING OTTO ANDERSON’S EXISTENTIAL CRISIS IN THE FILM A MAN CALLED OTTO - Pratiwi, Winda; Rosalinah, Yanti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
The examination of existential crisis in film has gained increasing relevance as cinema provides a representational space capable of illuminating complex human struggles with meaning, suffering, and psychological disorientation. In this context, the present study aims to analyze the construction of existential crisis and psychological recovery experienced by the protagonist Otto Anderson in the 2022 film A Man Called Otto. Employing a qualitative approach through interpretive textual analysis, this study aims to analyze key scenes, dialogues, and character developments that depict Otto’s existential rupture and subsequent transformation. The analysis is guided by Irvin D. Yalom’s Existential Psychotherapy, which outlines the four fundamental existential conditions, and Viktor Frankl’s Logotherapy, which emphasizes meaning reconstruction through creative, experiential, and attitudinal values. Findings reveal that the film portrays Otto’s existential crisis through his encounters with loss, isolation, and diminished purpose, expressed in pervasive despair and withdrawal. The study further demonstrates that Otto’s psychological recovery unfolds through the gradual restoration of meaning facilitated by relational connectedness, prosocial engagement, and the capacity to transcend personal suffering. This research highlights the potential of cinematic narratives to serve as interpretive sites for examining meaning-making processes and existential transformation within contemporary human experience.